2014
DOI: 10.1152/ajpendo.00337.2014
|View full text |Cite
|
Sign up to set email alerts
|

Insulin secretion stimulated by l-arginine and its metabolite l-ornithine depends on Gαi2

Abstract: detella pertussis toxin (PTx), also known as islet-activating protein, induces insulin secretion by ADP-ribosylation of inhibitory G proteins. PTx-induced insulin secretion may result either from inactivation of G␣o proteins or from combined inactivation of G␣o, G␣i1, G␣i2, and G␣i3 isoforms. However, the specific role of G␣i2 in pancreatic ␤-cells still remains unknown. In global (G␣i2 Ϫ/Ϫ ) and ␤-cell-specific (G␣ i2 ␤cko ) gene-targeted G␣i2 mouse models, we studied glucose homeostasis and islet functions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 43 publications
0
23
0
1
Order By: Relevance
“…A specific deletion of Gnai3 or Gnai2 in the inner ear and telencephalon was achieved by crossing Gnai3 fl/fl or Gnai2 fl/fl mice and Foxg1-Cre mice. Gnai2 fl/fl mice were provided by the Comparative Medicine Branch of the National Institute of Environmental Health Sciences, North Carolina 27709 [25], backcrossed on a C57BL/6N background [26], and the FoxG1-Cre mouse line [27] was purchased from The Jackson Laboratory (Bar Harbor, ME, USA), on a C57BL/6N background. A tissue-specific mutant mouse line was generated where both Gnai genes were disrupted by crossing with the FoxG1-Cre mouse line.…”
Section: Gene Targeting and Mice For Generation Of Gnai3mentioning
confidence: 99%
See 1 more Smart Citation
“…A specific deletion of Gnai3 or Gnai2 in the inner ear and telencephalon was achieved by crossing Gnai3 fl/fl or Gnai2 fl/fl mice and Foxg1-Cre mice. Gnai2 fl/fl mice were provided by the Comparative Medicine Branch of the National Institute of Environmental Health Sciences, North Carolina 27709 [25], backcrossed on a C57BL/6N background [26], and the FoxG1-Cre mouse line [27] was purchased from The Jackson Laboratory (Bar Harbor, ME, USA), on a C57BL/6N background. A tissue-specific mutant mouse line was generated where both Gnai genes were disrupted by crossing with the FoxG1-Cre mouse line.…”
Section: Gene Targeting and Mice For Generation Of Gnai3mentioning
confidence: 99%
“…Subsequently, the mouse strains were backcrossed on a C57BL/6N background for at least nine generations [26,29]. The Gnai2 mutant mouse line was kept in Individually Ventilated Cages (IVC), while the Gnai3 mutant mouse line was kept under SPF conditions.…”
Section: Gene Targeting and Mice For Generation Of Gnai3mentioning
confidence: 99%
“…Up-Regulated Gα i3 Partially Compensates for the Missing Gα i2 . Deletion of one Gα i isoform in mice can provoke an up-regulation of the expression levels of the remaining isoforms, which may substitute for some but not all functions (17,19,(29)(30)(31)(32)(33)). Because we observed a clear-cut phenotype in the Gα i2 KO mice, we analyzed the expression of Gα i isoforms in their platelets.…”
Section: Resultsmentioning
confidence: 99%
“…To clarify the mechanism, further studies are needed. Although ornithine is known to promote insulin-like growth factor (47) , Leiss et al (48) recently reported that ornithine can also stimulate insulin secretion via Gα i2 , belonging to the G-protein family. Taken together, we consider that ornithine increased by #4019 ingestion contribute to the promotion of insulin secretion from the pancreas.…”
Section: Discussionmentioning
confidence: 99%